Lagos : the development of an African city - Aderibigbe, A. B.; Ajayi, J. F. A. (Nigeria : Longman, 1975)
This volume collects together historical and contemporary studies of the Lagos urban area.
Includes bibliographical references p. 227-276
hza 29/01/2019
Loans
Keywords: Nigeria--Lagos; Urbanization; Economic development (Nigeria); Nigeria